Cryohemolysis of Human Fetal Erythrocytes in Hypertonic Medium of Electrolyte - Kuleshova, L. G. (Problems of Cryobiology and Cryomedicine, 2004)
The cryohemolysis of human fetal erythrocytes depending on the duration of cell exposure under room temperature in NaCl hypertonic solutions was studied using spectrophotometry method. These cells were found to become cooling-sensitive in NaCl media, where an osmolarity exceeded 840 mOsm/l (0.45 M).